رواية إعدام رئيس دراسة في تداخل الأجناس - عواد, أحمد الدندن (Université de M'sila, 2015)
غدت ظاهرة تداخل الأجناسمن الظاهر الأدبية التي سطعت في حقل النقد الأدبي الحديث ،وبات النص الروائي نصا مفتوحا ومشرعا لعديد من الأجناس على تعددها واختلافها. يهدف هذا البحث إلى الوقوف على ظاهرة تداخل الرواية والمقال في رواية إعدام الرئيس ، لما تختويه هذه الرواية من تقنيات ومرجعيات خاصة بفن المقالة والخبر بأنواعه ومغايرتها للانماط الروائية السابقة ، فقد مثّلت مرحلة الألفية الجديدة نقلة نوعية في مسيرة السرد الروائي ، فيها الأحداث السياسية والتقلبات في مركز السلكةن معين الادباء والمتاب الذي لا ينضب ووجد الباحث في هذه الرواية - إعدام الرئيس - نمطا سرديا جديدا ، وفلسفة جديدة في الطرح والتشكيل والبناء ،وبات النص الروائي فيها مفتوحا على مصرعيه ،متضمنا جنس المقالة من خلال عناصرها وموضوعاتها وسماتها. This research aims at identifying and studying the overlapping of different literary genres in the jordanian novel, taking the novel and the article as models. The study focuses on the postmodern era, especially with the beginning of the new Millennium, specifically between 2000-2013. During this time, the011 overlapping of literary genres in the jordanian novel witnessed a qualitative transition and a new phase in its structure and narrative style. Also during this period of time, the political events and the fluctuations in the political centers of power formed an inexhaustible source of topics for writers and critics as well, making the article, which primarily deals with politics, an indispensable and an inseparable form of art from the art of the novel. At this stage, the researcher found a multiplicity of patterns in the narrative styles, and new themes, structures, and forms within the jordanian novels, making it tolerant and open to include other forms of literary genres like the article as one of the most important and common forms of expressive arts due to its attachment to the media and the press in general. This popularity of the article as a literary genre in the postmodern era made it necessary for the jordanian novel to make use of it to develop its artistic structure, themes, and narrative style. The researcher finds it necessary to critically study and research this new literary phenomenon.
Keywords: الأدب الحديث- التجريب- تداخل الأجناس- النص- المفتوح المقالة- الواية experimentation, narrative styles, open text, jordanian novel.